Safety of dipeptidyl peptidase-4 inhibitors in older adults with type 2 diabetes: a systematic review and meta-analysis of randomized controlled trials. (January 2022) - Doni, Katharina; Bühn, Stefanie; Weise, Alina; Mann, Nina-Kristin; Hess, Simone; Sönnichsen, Andreas; Pieper, Dawid; Thürmann, Petra; Mathes, Tim
Registration: PROSPERO: CRD42020210645 Introduction: We aimed to assess the safety of dipeptidyl peptidase-4 (DPP-4) inhibitors in older patients with type 2 diabetes with inadequate glycaemic control. Methods: We included randomized controlled trials (RCTs) in older (⩾65 years) patients with type 2 diabetes. The intervention group was randomized to treatment with any DPP-4 inhibitors. A systematic search in MEDLINE and Embase was performed in December 2020. For assessing the risk of bias, RoB 2 tool was applied. The quality of evidence was assessed using the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) approach. We pooled outcomes using random effects meta-analyses. Results: We identified 16 RCTs that included 19, 317 patients with a mean age of greater than 70 years. The mean HbA1c level ranged between 7.1 and 10.0 g/dl. Adding DPP-4 inhibitors to standard care alone may increase mortality slightly [risk ratio (RR) 1.04; 95% confidence interval (CI) 0.89–1.21]. Adding DPP-4 inhibitors to standard care increases the risk for hypoglycaemia (RR 1.08; 95% CI 1.01–1.16), but difference in overall adverse events is negligible. DPP-4 inhibitors added to standard care may reduce mortality compared with sulfonylureas (RR 0.88; 95% CI 0.75–1.04). DPP-4 inhibitors probably reduce the risk for hypoglycaemia compared with sulfonylureas (magnitude of effect not quantifiable because of heterogeneity) but difference in overall adverse events is negligible. There is insufficient evidence on hospitalizations, falls, fractures, renal impairment and pancreatitis. Conclusion: There is no evidence that DPP-4 inhibitors in addition to standard care decrease mortality but DPP-4 inhibitors increase hypoglycaemia risk. Second-line therapy in older patients should be considered cautiously even in drugs with a good safety profile such as DPP-4 inhibitors. In case second-line treatment is necessary, DPP-4 inhibitors appear to be preferable to sulfonylureas. Plain language summary: Safety of dipeptidyl peptidase-4 inhibitors in older adults with type 2 diabetes: Introduction: We performed the review to assess the safety of dipeptidyl peptidase-4 (DPP-4) inhibitors in older type 2 diabetes patients with blood sugar outside the normal level. Methods: To answer the question, we searched various electronic databases. We included studies in older (⩾65 years) patients with type 2 diabetes that assessed the safety of DPP-4 inhibitors. The data from the different studies were quantitatively summarized using statistical methods. We assessed the quality of the data to judge the certainty of the findings. Results: We identified 16 studies that included 19, 317 patients with a mean age greater than 70 years. The average blood sugar level of patients in the included studies was slightly or moderately increased. Adding DPP-4 inhibitors to standard care alone may increase mortality slightly. Adding DPP-4 inhibitors to standard care increases the risk for hypoglycaemia, but difference in overall adverse events is negligible. DPP-4 inhibitors added to standard care may reduce mortality compared with sulfonylureas. DPP-4s probably reduce the risk of hypoglycaemia compared with sulfonylureas (magnitude of effect not quantifiable because of heterogeneity) but difference in overall adverse events is negligible. There is insufficient evidence on hospitalizations, falls, fractures, renal impairment and pancreatitis. Conclusion: There is no evidence that DPP-4 inhibitors in addition to standard care decrease mortality but DPP-4 inhibitors increase the risk that blood sugar falls below normal. Adding DPP-4 inhibitorss to standard care in older patients should be considered cautiously even in drugs with a good safety profile such as DPP-4 inhibitors. In case additional treatment is necessary, DPP-4 inhibitors appear to be preferable to sulfonylureas.